Assessing the ability of children and parents to rate their nasal patency. A cross sectional study. (May 2022) - Calvo-Henriquez, Christian; Martínez-Seijas, Pedro; Boronat-Catalá, Borja; Faraldo-García, Ana; Martínez-Capoccioni, Gabriel; Alobid, Isam; Banegassi, Ivan Mendez; Martin-Martin, Carlos
Abstract: Objective: Nasal obstruction is a common complaint in pediatric otolaryngology. There are several concerns about how nasal obstruction should be measured. This debate is even more important in children, as they can experience difficulties in being sensitive to their symptoms or even expressing them. In this research we aim to explore the ability of children (and their parents) to assess their nasal obstruction. Participants: AND METHODS: An observational cross-sectional study was performed. Four cohorts of children were consecutively selected from a third level referral Hospital. Cohort A (children suffering solely turbinate enlargement), B (adenoid enlargement only), and C (adenoid and turbinate enlargement), while cohort D were healthy controls. Children and parents were asked to rate nasal patency through a Likert scale from 0 (no patency, complete obstruction of the nose) to 10 (complete patency, it is easy to breathe through the nose). All participants underwent rhinomanometry. Results of nasal resistance were relativized according to pediatric reference values per each age subgroup. Results: 146 participants were included. Cohort A (54), B (40), C (28), D (24). There is a poor but significant correlation between parents' assessment and nasal resistance (rho = −0.28; p = 0.004). In children, there is no significant correlation with nasal resistance (rho = −0.14; p = 0.17). Stratified by severity, only children (and their parents) with good nasal breathing demonstrated good correlation values with the visual analogue score (VAS). Stratified by age, the correlation is only significant for parents of children older than 12 years old. Conclusions: This study has demonstrated a good ability to rate nasal patency by healthy children and their parents, but a poor ability for children suffering from impaired nasal breathing. We suggest combining subjective assessment of nasal patency with objective measurements such as rhinomanometry in children.